Microvascular Impairment in Patients With Cerebral Small Vessel Disease Assessed With Arterial Spin Labeling Magnetic Resonance Imaging: A Pilot Study - Neumann, Katja; Günther, Matthias; Düzel, Emrah; Schreiber, Stefanie (Frontiers in aging neuroscience, 2022)
In this pilot study, we investigated microvascular impairment in patients with cerebral small vessel disease (CSVD) using non-invasive arterial spin labeling (ASL) magnetic resonance imaging (MRI). This method enabled us to measure the perfusion parameters, cerebral blood flow (CBF), and arterial transit time (ATT), and the effective T1-relaxation time (T1eff) to research a novel approach of assessing perivascular clearance. CSVD severity was characterized using the Standards for Reporting Vascular Changes on Neuroimaging (STRIVE) and included a rating of white matter hyperintensities (WMHs), lacunes, enlarged perivascular spaces (EPVSs), and cerebral microbleeds (CMBs). Here, we found that CBF decreases and ATT increases with increasing CSVD severity in patients, most prominent for a white matter (WM) region-of-interest, whereas this relation was almost equally driven by WMHs, lacunes, EPVSs, and CMBs. Additionally, we observed a longer mean T1eff of gray matter and WM in patients with CSVD compared to elderly controls, providing an indication of impaired clearance in patients. Mainly T1eff of WM was associated with CSVD burden, whereas lobar lacunes and CMBs contributed primary to this relation compared to EPVSs of the centrum semiovale. Our results complement previous findings of CSVD-related hypoperfusion by the observation of retarded arterial blood arrival times in brain tissue and by an increased T1eff as potential indication of impaired clearance rates using ASL.